Distributed prescribed-time attitude consensus for multiple spacecraft via quantized communication - Xu, Chuang (2023)
This paper investigates the problem of prescribed-time attitude consensus for multiple spacecraft under directed graph subject to limited communication bandwidth and input saturation. First, a quantized communication mechanism that transmits quantized states only when their values change is developed to deal with the limited communication bandwidth, which can markedly reduce communication burden. Under the quantized communication, a distributed prescribed-time observer is designed for each follower spacecraft to estimate the leader spacecraft's state. This observer can guarantee the observed values converge to the leader spacecraft's state in a user-defined time. Then, we design a prescribed-time sliding manifold by using the observed values. Next, a prescribed-time attitude control law is designed based on the proposed sliding manifold. The prescribed-time stability of multiple spacecraft system subject to input saturation is proved, and the simulation results highlight the effectiveness of the scheme.